Case report: A rare case of hereditary hemochromatosis caused by a mutation in the HAMP gene in Fuyang, China - Wang, Jinling; Xu, Jing; Jiang, Ning; Liu, Hui; Li, Fengcheng; Wang, Beibei; Wang, Jin; Chu, Ziyu; Tan, Lin; Li, Shasha (Frontiers in Medicine, 2024)
Hemochromatosis, also known as siderosis, is a disease caused by excessive iron deposition in human organs and tissues, resulting from iron metabolism disorders. It is clinically characterized by skin pigmentation (bronze color), liver cirrhosis, diabetes, weakness, and fatigue. Additional symptoms may include arthritis, hypothyroidism, heart failure, and sexual hypofunction. Clinical manifestations can vary from person to person, with a few patients showing no clinical manifestations, which makes the diagnosis difficult for clinicians. In this case report, we described hereditary hemochromatosis related to a mutation in the HAMP gene in Fuyang City, China, as a reference for clinicians. Hereditary hemochromatosis is rarely reported in China. Clinicians in China have relatively insufficient knowledge of this disease, which leads to frequent misdiagnosis. In this case report, we describe hereditary hemochromatosis related to HAMP gene mutation in Fuyang City, China, for the clinician’s reference.